Non-destructive diagnosis of grounding grids based on the electromagnetic induction impedance method. (16th July 2021) - Song, Hengli; Dong, Haobin; Wang, Xin; Tang, Liangliang
Abstract: When attempting to detect faults in grounding grids, the electromagnetic induction method is hampered by the failure of fault diagnosis based on magnetic flux density detection. An electromagnetic induction impedance method is proposed to diagnose corrosion faults by detecting the induced impedance. A non-destructive testing prototype was developed. The sensor of the prototype consists of biaxial sensing coils, a frequency selection module, and a dual-channel synchronous demodulator. The biaxial sensing coils are configured as four identical coils forming a cross. This symmetrical structure realizes the detection of unknown topological structures in grounding grids. The frequency selection module improves the signal-to-noise ratio of the system. The digital demodulator synchronously extracts the phase information in two orthogonal directions. The key technical indicators of the prototype, such as the frequency characteristics, the amplitude accuracy, the phase accuracy, the interference resistance, and the amplitude consistency between channels are tested. Experiments were carried out on a real-size physical model, corroded samples, and an actual operating substation. The results confirm the feasibility of the method and the prototype for the detection of topological structures, disconnections, and faults in grounding grids.